Female prostate: historical, developmental, and morphological perspectives. (4th May 2017) - Biancardi, Manoel F.; dos Santos, Fernanda C. A.; de Carvalho, Hernandes F.; Sanches, Bruno D. A.; Taboga, Sebastião R.
Abstract: The female prostate was first described by Reijnier de Graaf in 1672, and even after several years this gland is still a matter of controversy. Part of this is because the biological function of this female gland is unclear. Moreover, when compared with the male prostate, the existence of this organ in females does not make sense, mainly when we consider that the major function of this gland is to produce a secretion that is responsible for guarantee the sperm survival and assure the reproductive success. However, even under a controversy field, we now have a lot of scientific information which enhances our knowledge of several important biological aspects of this gland. It is clear that this gland is found in some female mammals including humans, rodents, rabbits, bats, and dogs. Several studies with rodents showed that the female prostate is homolog of the male prostate, showing strong macroscopic and microscopic similarities with the ventral lobe of males. Besides these aspects, there are several studies reporting that diseases such as cysts, hyperplasia, and carcinoma may affect the female prostate. Therefore, although diseases involving the female prostate are rare, the susceptibility of this organ to develop lesions must be considered, especially in our recent years in which the exposure to endocrine‐disrupting chemicals has greatly increased. Finally, further studies will be necessary to enhance our understanding about this gland, mainly of the developmental, evolutionary, and biological functions.